Blood Collection for Autologous Blood-Derived Product Preparation: Technique & Application - Alan George, DDS; Thomas Johnson (Elsevier, 2024)
OBJECTIVES: 1. Describe an armamentarium and protocol for safely obtaining blood samples for ABP preparation. 2. Demonstrate sample volumes typically needed in periodontics through case presentation. METHODS: Patients in this report presented to the Department of Periodontics, Army Postgraduate Dental School (APDS) Postgraduate Dental College, Fort Eisenhower, Georgia. All patients received intravenous cannulation for moderate sedation and elected to provide blood samples for PRF preparation using the described protocol. In all cases, a single 20-gauge intravenous catheter was used for both blood collection and fluid/medication delivery. CONCLUSIONS: Blood volumes required for ABP preparation amount to a fraction of published recommended total blood draw volume limits. The blood collection method described in this report, which is consistent with published standards of practice, necessitates few additional steps and supplies for practitioners already placing peripheral IV catheters. IMPLICATIONS: This report serves as a concise protocol for safe and efficient preparation of ABPs that minimizes patient morbidity by utilizing a single intravenous catheter.